2012
DOI: 10.1063/1.4764104
|View full text |Cite
|
Sign up to set email alerts
|

The analytical basis for the resonances and anti-resonances of loop antennas and meta-material ring resonators

Abstract: Alfvén eigenmodes excitation by external loop antennas in the Compact Helical System heliotron/torsatron Rev. Sci. Instrum. 72, 405 (2001);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…In contrast to a resonance, the most important signature of an anti-resonance is a π phase jump accompanied by a pronounced low magnitude in transmission. Similar to resonances, anti-resonances widely exist in nearly all kinds of dynamic systems from mechanical oscillators [41,42] to electrodynamic [43][44][45][46][47] and quantum systems [48][49][50][51]. Generally, the anti-resonance arises from destructive interference between the excitation and response of the system, which is different from the constructive interference during resonance.…”
Section: The Physics Of An Anti-resonancementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to a resonance, the most important signature of an anti-resonance is a π phase jump accompanied by a pronounced low magnitude in transmission. Similar to resonances, anti-resonances widely exist in nearly all kinds of dynamic systems from mechanical oscillators [41,42] to electrodynamic [43][44][45][46][47] and quantum systems [48][49][50][51]. Generally, the anti-resonance arises from destructive interference between the excitation and response of the system, which is different from the constructive interference during resonance.…”
Section: The Physics Of An Anti-resonancementioning
confidence: 99%
“…Phenomenologically, anti-resonance in the transmission spectrum of a given microwave cavity can be treated as an equivalent parallel RLC circuit [45], which effectively blocks the incident signal at the resonant frequency due to its high impedance [45,46]. For cavity resonance in the transmission spectrum, closed boundaries defined by discontinuous interfaces, such as the metallic walls of cavity, determine the resonant behavior.…”
Section: Input-output Formalism For a Cavity Anti-resonancementioning
confidence: 99%
“…This is an extension of an earlier work, which formulated the input impedance in the RF region as a RLC circuit representation. 30 In that work, we showed that the results also extended to the high GHz regime. In order to extend the RLC model to the NIR and OR, we derive additional terms, so that the modal RLC elements of circular loops, constructed of metals, dielectrics, or semi-conductors can now be calculated at any wavelength from the RF through the OR.…”
Section: Introductionmentioning
confidence: 69%
“…An analytic form for its input impedance has been known since the mid-1950s. 31,32 In a recent paper, 30 we derived a simplified form by recasting the formulation as a RLC model. We showed that the loop looks like an infinite set of series resonant circuits in parallel…”
Section: A Review Of Closed Loop Theory At Low Frequenciesmentioning
confidence: 99%
“…This makes them inappropriate for communication on a single frequency, as needed in the RF. In fact, a detailed, analytical, circuit model of the large loop was not developed until 2012 [2].…”
Section: Introductionmentioning
confidence: 99%